The Functional and Molecular Effects of Doxycycline Treatment on Borrelia burgdorferi Phenotype - Caskey, John R.; Hasenkampf, Nicole R.; Martin, Dale S.; Chouljenko, Vladimir N.; Subramanian, Ramesh; Cheslock, Mercedes A.; Embers, Monica E. (Frontiers in Microbiology, 2019)
Recent studies have shown that Borrelia burgdorferi can form antibiotic -tolerant persisters in the presence of microbiostatic drugs such as doxycycline. Precisely how this occurs is yet unknown. Our goal was to examine gene transcription by B. burgdorferi following doxycycline treatment in an effort to identify both persister-associated genes and possible targets for antimicrobial intervention. To do so, we performed next-generation RNA sequencing on doxycycline-treated spirochetes and treated spirochetes following regrowth, comparing them to untreated B. burgdorferi. A number of genes were perturbed and most of those which were statistically significant were down-regulated in the treated versus the untreated or treated/re-grown. Genes upregulated in the treated B. burgdorferi included a number of Erp genes and rplU, a 50S ribosomal protein. Among those genes associated with post-treatment regrowth were bba74 (Osm28), bba03, several peptide ABC transporters, ospA, ospB, ospC, dbpA and bba62. Studies are underway to determine if these same genes are perturbed in B. burgdorferi treated with doxycycline in a host environment.